Analisis Prediksi Fragmentasi Peledakan Tambang Terbuka dengan Menggunakan Model Rock Engineering System (RES) dan Optimasi Geometri Peledakan untuk Mencapai Target Produktivitas Alat Gali Muat pada Kegiatan Pembongkaran Tanah Penutup (Overburden) di PT Kalimantan Prima Persada Job Site BDMA Kalimantan Uta - Aldo Mahyandra; Dedi Yulhendra (Departemen Teknik Pertambangan FT UNP, 2020)
Abstract. The blasting process will produce rocks fragmentation. Thus, there is the possibility of risk of fragmentation, such as boulder size, loading process, and productivity of the equipment cannot be achieved. The Rock Engineering System (RES) is a predictive model for blasting rock fragmentation. This study uses 10 effective parameters that affect rock fragmentation. The data that has been collected is as much as 30 blasting, carried out at PT KPP Job Site BDMA, North Kalimantan. The prediction of fragmentation in this study also uses the Kuz Ram method and a modification from Cunningham (2005) as comparison data. To validate the method that has been used, the correlation coefficient (R2) and the Root Mean Square Error (RMSE) will be analyzed between the actual measurements using split desktop software and the prediction method used. Between the RES model, the Kuz Ram method, and Cunningham method, the R2 value is obtained with a very strong relationship, are 0.97 in area 1 and 0.88 in area 2, and a low RMSE value are 24.31 in area 1 and 10.78 in area 2 using the RES model. So, based on this, the writer can make a blasting geometry to achieve productivity from the 2 theories used (R.L Ash and C.J Konya). Finally, geometries of R.L Ash is a best choice.Keywords : Rock Engineering System, Productivity, Statistic Analisys, R.L Ash, C.J. Konya